From Saline to Freshwater: The Diversity of Western Lakes in Space and Time 2021
DOI: 10.1130/2020.2536(19)
|View full text |Cite
|
Sign up to set email alerts
|

Holocene sedimentary architecture and paleoclimate variability at Mono Lake, California

Abstract: Mono Lake occupies an internally drained basin on the eastern flank of the Sierra Nevada, and it is sensitive to climatic changes affecting precipitation in the mountains (largely delivered in the form of snowpack). Efforts to recover cores from the lake have been impeded by coarse tephra erupted from the Mono Craters, and by disruption of the lake floor due to the uplift of Paoha Island ~300 yr ago. In this study, we describe the stratigraphy of cores from three recent campaigns, in 2007, 2009, and 2010, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 117 publications
1
11
0
Order By: Relevance
“…1C) in 18-m water depth (Hodelka et al, 2020). Here, we present an age-depth model based on 23 accelerator mass-spectrometry radiocarbon dates, measured from plant macrofossils, charcoal, pollen purified by flow cytometry, and four tephra correlations (Hodelka et al, 2020; Tunno et al, 2021; Zimmerman et al, 2021; Table 1). Our Bacon age-depth model has been updated from the previous MONO15 age model presented by Hodelka et al (2020) by including four new radiocarbon dates conducted for this study (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1C) in 18-m water depth (Hodelka et al, 2020). Here, we present an age-depth model based on 23 accelerator mass-spectrometry radiocarbon dates, measured from plant macrofossils, charcoal, pollen purified by flow cytometry, and four tephra correlations (Hodelka et al, 2020; Tunno et al, 2021; Zimmerman et al, 2021; Table 1). Our Bacon age-depth model has been updated from the previous MONO15 age model presented by Hodelka et al (2020) by including four new radiocarbon dates conducted for this study (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…† New radiocarbon dates not presented by Hodelka et al (2020). *Dates from tephra from BINGO-MONO10-4A core were acquired via 14 C AMS dating and discussed in Hodelka et al (2020) and Zimmerman et al (2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pigati and Springer (2022) concluded that the Death Valley paleowetland deposits confirmed that two distinct phases of the YD linked to changes in the Atlantic Meridional Overturning Circulation observed elsewhere also extended into the southwestern USA. Ostracodes and the sedimentology from Mono Ali (2018) and relative lake-level indicator Ca:Ti (red) data from the shallow-water BINGO10 sediment core (Zimmerman et al, 2020). The dashed line at 1945 masl indicates modern lake level.…”
Section: Taphonomy and Linked Landscape-lakescape Processesmentioning
confidence: 99%
“…Figure 9. (Top) Absolute paleoshoreline elevation data fromAli (2018) and relative lake-level indicator Ca:Ti (red) data from the shallow-water BINGO10 sediment core(Zimmerman et al, 2020). The dashed line at 1945 masl indicates modern lake level.…”
mentioning
confidence: 99%